Introduction to non-Marxism - Laruelle, François (Univocal Publishing, 2015)
Following the collapse of the communist states it was assumed that Marxist philosophy had collapsed with it. In Introduction to Non-Marxism, François Laruelle aims to recover Marxism along with its failure by asking the question "What is to be done with Marxism itself?" To answer, Laruelle resists the temptation to make Marxism more palatable after the death of metaphysics by transforming Marxism into a mere social science or by simply embracing with evangelical fervor the idea of communism. Instead Laruelle proposes a heretical science of Marxism that will investigate Marxism in both its failure and power so as to fashion new theoretical tools. In the course of engaging with the material of Marxism, Laruelle takes on the philosophy of Marx along with important philosophers who have extended that philosophy including Althusser, Balibar, Negri as well as the attempt at a phenomenological Marxism found in the work of Michel Henry. Through this engagement Laruelle develops with great precision the history and function of his concept of determination-in-the-last-instance. In the midst of the assumed failure of Marxism and the defections and resentment that followed, Laruelle's non-Marxism responds with the bold declaration: "Do not give up on theory!"--Provided by publisher.